The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1038/sj.hdy.6883490
|View full text |Cite
|
Sign up to set email alerts
|

Species-wide homogeneity of nuclear ribosomal ITS2 sequences in the spider mite Tetranychus urticae contrasts with extensive mitochondrial COI polymorphism

Abstract: We compared patterns of intraspecific polymorphism of two markers with contrasted modes of evolution, nuclear ribosomal DNA (rDNA) and mitochondrial DNA (mtDNA), in the phytophagous mite Tetranychus urticae Koch. The second internal transcribed spacer (ITS2) of rDNA and a fragment in the mtDNA gene coding for Cytochrome Oxidase I (COI), were PCR-amplified and sequenced in samples of various geographical origins distributed worldwide. The 15 COI haplotypes found fell into two major phylogenetic lineages differi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 9 publications
2
54
1
4
Order By: Relevance
“…In addition, Zahler et al (1998) and Essig et al (1999) were not able to find clear differences within the worldwide distributed genera Psoroptes and Chorioptes, respectively. However, Navajas et al (1998) showed extensive polymorphism in sequences of mitochondrial cytochrome oxidase I in T. urticae. Some sorts of geographical or host specificity in Sarcoptes populations have been shown in studies in which microsatellites were used as markers (Walton et al, 2004;Soglia et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Zahler et al (1998) and Essig et al (1999) were not able to find clear differences within the worldwide distributed genera Psoroptes and Chorioptes, respectively. However, Navajas et al (1998) showed extensive polymorphism in sequences of mitochondrial cytochrome oxidase I in T. urticae. Some sorts of geographical or host specificity in Sarcoptes populations have been shown in studies in which microsatellites were used as markers (Walton et al, 2004;Soglia et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The number of variable sites was very different among populations: the population ItNWVv was the most variable (30 mutations), whereas the ItNWMf (4 mutations) and SpNEVv (5 mutations ITS-2 rDNA appears to be suitable genetic marker for distinguishing closely related species and examining phylogenetic relationships within genera but not suitable for genetic characterization within a species for mites (Navajas et al, 1994(Navajas et al, , 1998Navajas and Fenton, 2000;Zahler et al, 1998Zahler et al, , 1999Essig et al, 1999;Berrilli et al, 2002). For example, Navajas et al (1998 found very low variation in ITS-2 sequences within Tetranychus urticae. Similar patterns of variation were found by Navajas et al (1994) for Mononychellus progresivus and, as mentioned above, by Zahler et al (1999) and Berrilli et al (2002) for Sarcoptes.…”
Section: Resultsmentioning
confidence: 99%
“…According to extraction methods already published for various acari (Eriophyidae, Ixodidae, Laelapidae, Phytoseiidae, Tetranychidae, Trombidiidae), we chose and compared three conventional methods for extracting DNA from D. gallinae: a CTAB method, with a lysis step followed by a phenol chloroform precipitation [17,20], a Qiamp DNA extraction kit using separation with a column [8,11], and a Chelex resin [10,14,21,25,28,29]. Another attractive method, the FTA technology, was also tested, and compared to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the molecular genetics of this group of sand flies (Esseghir et al, 1997;Ready et al, 1997Ready et al, , 1998Ishikawa et al, 1999). However, studies of the molecular phylogenetics of other arthropod groups suggest that sequence from region I of the mitochondrial cytochrome c oxidase I (COI) gene might be informative for clarifying Lutzomyia taxonomy at the species level (Navajas et al, 1994(Navajas et al, , 1996(Navajas et al, , 1998Roderick and Gillespie, 1998). Here, we present a phylogeographical interpretation of L. longipalpis based on molecular phylogenetic analysis using mtDNA and available theories on the historical physical geography of Central and South America (Haffer, 1969;Howe, 1974;Keigwin, 1978;Haffer, 1981;Rod, 1981;Sykes et al, 1982;Stehli and Webb, 1985;Hoorn, 1994;Hoorn et al, 1995).…”
Section: Introductionmentioning
confidence: 99%